Social traps and ethical dilemmas: an Islamic perspective - Fontaine, Rodrigue (2010)
This study looks at the usefulness of 5 hadith to allow Muslim managers to effectively manage social traps and ethical dilemmas. These hadith are: "actions are but by intentions", "the religion is naseeha", "the lawful is clear and the forbidden is clear", "there is no harming and no reciprocating of harm" and "whatever I forbid, stay away from. Whatever I order, do as much as you can". Examples of social traps and ethical dilemmas are given to illustrate.